Parking Levy Policy Innovation in Malang City: From Cash-Based Collection to Virtual Accounts - Dody Setyawan; Cahyo Sasmito; Merdiana Loda Nangi (Journal of Transformative Governance and Social Justice, 2026)
Parking levy management is an important component of local revenue governance because it contributes to locally generated revenue. However, conventional cash-based collection systems continue to face governance challenges, including revenue leakage, delayed reporting, and limited monitoring capacity. This study analyzes the implementation of a parking levy policy innovation through a Virtual Account payment system integrated with the Regional General Treasury Account (RKUD) in Malang City and identifies the factors supporting and constraining its implementation. A descriptive qualitative approach was employed using observation, in-depth interviews, and document analysis. The participants consisted of the Head of the Transportation Agency, the Head of the Parking Management Division, field supervisors, official parking attendants, and parking service users selected through purposive sampling. The analysis draws on the perspectives of policy innovation and digital governance to explain how digital payment transformation strengthens accountability and local revenue governance. The findings indicate that the Virtual Account system transaction traceability, strengthened monitoring mechanisms, enhanced administrative order, and reduced opportunities for revenue leakage. Nevertheless, several challenges remain, including limited performance evaluation, continued reliance on manual field supervision, and uneven compliance among parking attendants. The findings demonstrate that the digitalization of parking levy collection strengthens local revenue governance, although improvements in evaluation and supervisory mechanisms remain necessary.